Advances in Production Technology - Brecher, Christian (Lecture Notes in Production Engineering, 2015)
This edited volume contains the selected papers presented at the scientific board meeting of the German Cluster of Excellence on “Integrative Production Technology for High-Wage Countries”,  held in November 2014. The topical structure of the book is clustered in six sessions: Integrative Production Technology, Individualised Production, Virtual Production Systems, Integrated Technologies, Self-Optimising Production Systems and Human Factors in Production Technology. The Aachen perspective on a holistic theory of production is complemented by conference papers from external leading researchers in the fields of production, materials science and bordering disciplines. The target audience primarily comprises research experts and practitioners in the field but the book may also be beneficial for graduate students.